2003
DOI: 10.1007/s00330-003-1915-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pulmonary nodules by multislice computed tomography: improved detection rate with reduced slice thickness

Abstract: The purpose of this study was to find out if the use of 1.25-mm collimated thin-slice technique helps to detect more small pulmonary lung nodules than the use of 5 mm. A total of 100 patient examinations that allowed a reconstruction of 1.25-mm slice thickness in addition to the standard of 5-mm slices were included in a prospective study. Acquisition technique included four rows of 1-mm slices. Two sets of contiguous images were reconstructed and compared with 1.25- and 5-mm slice thickness, respectively. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(114 citation statements)
references
References 23 publications
(29 reference statements)
2
102
0
7
Order By: Relevance
“…Referral bias might have increased the proportion of patients with more severe disease. Finally, a variety of previous CT techniques have been superseded by new developments [19]. In the future, the use of higher resolution images by reducing the slice thickness or applying a higher spatial resolution reconstruction algorithm technique may allow the better understanding of the outcome of MAC pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Referral bias might have increased the proportion of patients with more severe disease. Finally, a variety of previous CT techniques have been superseded by new developments [19]. In the future, the use of higher resolution images by reducing the slice thickness or applying a higher spatial resolution reconstruction algorithm technique may allow the better understanding of the outcome of MAC pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…In most routine PET/CT scans, the images are reconstructed using a relatively thick slices (typically 5 mm), with soft tissue reconstruction algorithm. Prior studies have demonstrated that using thinner slices (1.25 mm) can improve the rate of pulmonary nodule detection on routine BH-CT (15). At our institution, we commonly reformat CT images from PET/CT studies with a high-resolution reconstruction to improve the detection of pulmonary nodules, although the added value from these reformations is unknown.…”
mentioning
confidence: 99%
“…In 2000s, multi-detector row CT was used in screening programs, a CT exam can scan the entire thorax to acquire thin-section images in less than 10 seconds (15). Depending on the screening, the radiologists can get multiple spiral data during a single CT screening that helps them to generate clear CT images of different section thickness, even very small lung nodules.…”
Section: Review Articlementioning
confidence: 99%